Correlation of Parasite Burden, kDNA Integration, Autoreactive Antibodies, and Cytokine Pattern in the Pathophysiology of Chagas Disease - Wesley, Moisés; Moraes, Aline; Rosa, Ana de Cássia; Lott Carvalho, Juliana; Shiroma, Tatiana; Vital, Tamires; Dias, Nayra; de Carvalho, Bruna; do Amaral Rabello, Doralina; Borges, Tatiana Karla dos Santos; Dallago, Bruno; Nitz, Nadjar; et al. (Frontiers in Microbiology, 2019)
Chagas disease (CD), caused by the protozoan Trypanosoma cruzi (T. cruzi), is the main parasitic disease in the Western Hemisphere. Unfortunately, its physiopathology is not completely understood, and cardiomegaly development is hard to predict. Trying to explain tissue lesion and the fact that only a percentage of the infected individuals develops clinical manifestations, a variety of mechanisms have been suggested as the provokers of CD, such as parasite persistence and autoimmune responses. However, holistic analysis of how parasite and host-related elements may connect to each other and influence clinical outcome are still scarce in the literature. Here, we investigated murine models of CD caused by three different pathogen strains: Colombian, CL Brener and Y strains, and employed parasitological and immunological tests to determine parasite load, antibody reactivity, and cytokine production during the acute and chronic phases of the disease. Also, we developed a quantitative PCR (qPCR) protocol to quantify T. cruzi kDNA minicircle integration into the mammalian host genome. Finally, we used a robust correlation analysis to interconnect parasite- and host-related factors over time. Higher parasite load in the heart and in the intestine was significantly associated with IgG raised against host cardiac proteins. Also, increased heart and bone marrow parasitism was associated with a more intense leukocyte infiltration. kDNA integration rates correlated to the levels of IgG antibodies reactive to host cardiac proteins and interferon production, both influencing tissue inflammation. In conclusion, our results shed light into how inflammatory process associates with parasite load, kDNA transfer to the host, autoreactive autoantibody production and cytokine profile. Altogether, our data support the proposal of an updated integrative theory regarding CD pathophysiology.